2022
DOI: 10.3390/molecules27123934
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antileukemia Activity Evaluation of Benzophenanthridine Alkaloid Derivatives

Abstract: Thirty-three benzophenanthridine alkaloid derivatives (1a–1u and 2a–2l) were synthesized, and their cytotoxic activities against two leukemia cell lines (Jurkat Clone E6-1 and THP-1) were evaluated in vitro using a Cell Counting Kit-8 (CCK-8) assay. Nine of these derivatives (1i–l, 2a, and 2i–l) with IC50 values in the range of 0.18–7.94 μM showed significant inhibitory effects on the proliferation of both cancer cell lines. Analysis of the primary structure–activity relationships revealed that different subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The compounds chelerythrine (2), structurally modified to yield compounds 13-16, sanguinarine (1), and derivatives 8-12, exhibit potent activity against Jurkat clone e6-1 and THP-1 leukemia cell lines, with IC 50 values from 0.18 to 7.94 µM. Notably, most of the activities of the above compounds are higher than those of chelerythrine (2) and sanguinarine (1)'s original activities, in which the IC 50 values of compound 12 against the above two leukemia cell lines reach 0.53 ± 0.05 and 0.18 ± 0.03 µM, respectively [46]. Sanguinarine (1), chelerythrine (2), sanguilutine (3), sanguirubine (4), chelirubine (5), and macarpine (7) (Figure 1) exhibit antitumor activity against various cancer cell lines, Sanguinarine (1), chelerythrine (2), sanguilutine (3), sanguirubine (4), chelirubine (5), and macarpine (7) (Figure 1) exhibit antitumor activity against various cancer cell lines, Sanguinarine (1), chelerythrine (2), sanguilutine (3), sanguirubine (4), chelirubine (5), and macarpine (7) (Figure 1) exhibit antitumor activity against various cancer cell lines, 0.91 ± 0.04 1.17 ± 0.13…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From P...mentioning
confidence: 97%
See 2 more Smart Citations
“…The compounds chelerythrine (2), structurally modified to yield compounds 13-16, sanguinarine (1), and derivatives 8-12, exhibit potent activity against Jurkat clone e6-1 and THP-1 leukemia cell lines, with IC 50 values from 0.18 to 7.94 µM. Notably, most of the activities of the above compounds are higher than those of chelerythrine (2) and sanguinarine (1)'s original activities, in which the IC 50 values of compound 12 against the above two leukemia cell lines reach 0.53 ± 0.05 and 0.18 ± 0.03 µM, respectively [46]. Sanguinarine (1), chelerythrine (2), sanguilutine (3), sanguirubine (4), chelirubine (5), and macarpine (7) (Figure 1) exhibit antitumor activity against various cancer cell lines, Sanguinarine (1), chelerythrine (2), sanguilutine (3), sanguirubine (4), chelirubine (5), and macarpine (7) (Figure 1) exhibit antitumor activity against various cancer cell lines, Sanguinarine (1), chelerythrine (2), sanguilutine (3), sanguirubine (4), chelirubine (5), and macarpine (7) (Figure 1) exhibit antitumor activity against various cancer cell lines, 0.91 ± 0.04 1.17 ± 0.13…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From P...mentioning
confidence: 97%
“…The compounds chelerythrine (2), structurally modified to yield compounds 13-16, sanguinarine (1), and derivatives 8-12, exhibit potent activity against Jurkat clone e6-1 and THP-1 leukemia cell lines, with IC50 values from 0.18 to 7.94 µM. Notably, most of the activities of the above compounds are higher than those of chelerythrine (2) and sanguinarine (1)'s original activities, in which the IC50 values of compound 12 against the above two leukemia cell lines reach 0.53 ± 0.05 and 0.18 ± 0.03 µM, respectively [46]. The compounds chelerythrine (2), structurally modified to yield compounds 13-16, sanguinarine (1), and derivatives 8-12, exhibit potent activity against Jurkat clone e6-1 and THP-1 leukemia cell lines, with IC 50 values from 0.18 to 7.94 µM.…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From P...mentioning
confidence: 98%
See 1 more Smart Citation
“…According to previous research, 1 exerts its cytostatic effects mainly by inducing the apoptosis of tumor cells through regulatory proteins and signaling pathways, including the mitogen-activated protein kinase (MAPK) [11], PI3K/AKT [12], JAK2/STAT3, and P53 pathways [13,14]. However, it is not clear how these signaling pathways and proteins are To improve the cytostatic activity of 1 and reduce its toxic effects on normal cells, in our previous work we carried out structural modification and assessed the anti-leukemia activities of its derivatives [9]. We found that the activity of 1 was mainly dependent on the following structural features: the fusion of the B/C ring, hydroxylation patterns, N-methyl substitutions, and planar configuration [10].…”
Section: Introductionmentioning
confidence: 99%